2017
DOI: 10.1590/1678-992x-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme complex supplementation in different nutrient levels diets on pigs feces excretion and anaerobic digestion

Abstract: This research aimed to evaluate enzyme supplementation in diets with different nutritional levels for pigs in their feces excretion and anaerobic digestion. Fifty four gilts were placed on diets formulated to achieve 100 or 95 or 90 % of a pig's nutrient requirements, with the addition of an enzyme complex containing amylase, β-glucanase, cellulase, pectinase, xylanase, protease and phytase (diets 100E, 95E and 90E) or without the enzymes (diets 100, 95 and 90). The trial was divided into three periods (1, 1-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In our study, feeding multienzymes supplementations significantly changed the bacterial diversity in donkey feces and significantly increased ACE, Chao1, and Shannon indices. This is consistent with the research results of Yang et al in broilers [ 29 ]. With the addition of exogenous enzymes to feed, the bacterial diversity index improved in feces.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, feeding multienzymes supplementations significantly changed the bacterial diversity in donkey feces and significantly increased ACE, Chao1, and Shannon indices. This is consistent with the research results of Yang et al in broilers [ 29 ]. With the addition of exogenous enzymes to feed, the bacterial diversity index improved in feces.…”
Section: Discussionsupporting
confidence: 94%
“…A compound enzyme preparation is composed of one or several single enzyme preparations as the main body, mixed with other single enzyme preparations, or obtained through fermentation by one or several microorganisms. Studies have shown that adding a compound enzyme preparation to the feed can supplement the lack of endogenous enzyme secretion, effectively reduce the level of antinutritional factors in feed, improve the feed nutritional value, and promote the healthy growth of animals [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Ruiz et al (2017), carbohydrases, especially endoenzymes, release part of the molecules of fibrous carbohydrates that may be enzymatically used by the pig or its intestinal microbial population. Therefore, the carbohydrate portions released by the exogenous enzymes may be a source of energy for the animal or simply be excreted.…”
mentioning
confidence: 99%